Allelopathy and underlying mechanism of mango (Mangifera indica) peel extracts on Alexandrium catenella - Wang, Yanqun; Zang, Yu; Zhao, Wenxi; Xu, Mengxue; Bai, Jie; Li, Li (Frontiers in Plant Science, 2024)
Harmful algal blooms (HABs) have always been a worldwide environmental issue. The methods based on the principle of allelopathy provide a novel direction for controlling HABs; however, there are a few studies on the application of allelopathic algaecides to control harmful algae in marine environments. Here we examined the algicidal capacity of 15 fruit peel extracts with biological activity on Alexandrium catenella. The results displayed that the mango peel extracts (MPE) showed efficient inhibition on species growth. The algicidal rate reached 93.32 ± 0.56% at 96 h after adding 5 g/L MPE to the culture medium of A. catenella. Furthermore, we found that the expression of key genes involved in PSII and PSI was downregulated as well as obstructed the electron transportation in the light reaction process and the synthesis of organic matter. The blocked photosynthetic chain induced the accumulation of substantial reactive oxygen species, resulting in severe peroxidation of the membrane lipids. Simultaneously, the expression pattern of key genes involved in the fatty acid, amino acid, and peroxisome breakdown pathways was upregulated, which suggested that the synthesis and decomposition of intracellular organic matter may be in an imbalanced state. The results above indicated that oxidative damage and energy metabolism disequilibrium are two key pathways by which MPE induced algal cell death. Furthermore, several kinds of active substances and their proportion in MPE had been identified by liquid chromatography quadrupole time-of-flight mass spectrometry. It is speculated that esters may be the important component playing an algicidal effect. However, the specific substance that plays a key role in inhibiting the growth of A. catenella and the algicidal mechanism remain to be further studied. This study might provide a new direction in the management of HABs in the future.